Must Leadership Be Undemocratic? - Boaks, Jacqueline (2015)
Theories of leadership and democracy and their underlying assumptions both speak to our relationship to power. The core question common to discussions ranging from political legitimacy, to democracy, to Machiavellianism, to Platonism, is what, if any, power that some individuals have over others is (morally as well as legally) legitimate and why? At one extreme are cases such as Machiavellianism and political realism, which come close to suggesting that whatever actual power individuals or states can maintain as just is legitimate. At the other extreme is the sceptical position that believes no power of individuals over others is legitimate. Theories of leadership and democracy both offer alternative kinds of answers to this question, both accepting that some types are legitimate and with limiting factors. Both democracy and leadership can be seen as centrally including claims for the right and safe allocation of power.